UDP-Glucosyltransferases from Rice, Brachypodium, and Barley: Substrate Specificities and Synthesis of Type A and B Trichothecene-3-O-β-d-glucosides - Michlmayr, Herbert; Varga, Elisabeth; Malachová, Alexandra; Fruhmann, Philipp; Piątkowska, Marta; Hametner, Christian; Šofrová, Jana; Jaunecker, Günther; Häubl, Georg; Lemmens, Marc; Berthiller, Franz; Adam, Gerhard (Toxins, 2018)
Trichothecene toxins are confirmed or suspected virulence factors of various plant-pathogenic Fusarium species. Plants can detoxify these to a variable extent by glucosylation, a reaction catalyzed by UDP-glucosyltransferases (UGTs). Due to the unavailability of analytical standards for many trichothecene-glucoconjugates, information on such compounds is limited. Here, the previously identified deoxynivalenol-conjugating UGTs HvUGT13248 (barley), OsUGT79 (rice) and Bradi5g03300 (Brachypodium), were expressed in E. coli, affinity purified, and characterized towards their abilities to glucosylate the most relevant type A and B trichothecenes. HvUGT13248, which prefers nivalenol over deoxynivalenol, is also able to conjugate C-4 acetylated trichothecenes (e.g., T-2 toxin) to some degree while OsUGT79 and Bradi5g03300 are completely inactive with C-4 acetylated derivatives. The type A trichothecenes HT-2 toxin and T-2 triol are the kinetically preferred substrates in the case of HvUGT13248 and Bradi5g03300. We glucosylated several trichothecenes with OsUGT79 (HT-2 toxin, T-2 triol) and HvUGT13248 (T-2 toxin, neosolaniol, 4,15-diacetoxyscirpenol, fusarenon X) in the preparative scale. NMR analysis of the purified glucosides showed that exclusively β-D-glucosides were formed regio-selectively at position C-3-OH of the trichothecenes. These synthesized standards can be used to investigate the occurrence and toxicological properties of these modified mycotoxins.
Keywords: Glycosyltransferases; Plant Proteins; glukosidy; NMR; masked mycotoxin; Brachypodium; Glucosides; phase II detoxification; ječmen (rod); Trichothecenes; cereals; Oryza; trichotheceny; Hordeum; rostlinné proteiny; rýže (rod); glykosyltransferasy; Fusarium head blight